2021
DOI: 10.1002/hyp.14402
|View full text |Cite
|
Sign up to set email alerts
|

Dissolved inorganic carbon isotopes of a typical alpine river on the Tibetan Plateau revealing carbon sources, wetland effect and river recharge

Abstract: The Nyangqu River, the largest right bank tributary of the Yarlung Zangbo River in the Qinghai-Tibet Plateau, was representative of an alpine riverine carbon cycle experiencing climate change. In this study, dissolved inorganic carbon (DIC) spatial and seasonal variations, as well as their carbon isotopic compositions (δ 13 C DIC ) in river water and groundwater were systematically investigated to provide constraints on DIC sources, recharge and cycling. Significant changes in the δ 13 C DIC values (from À2.9‰… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 52 publications
0
2
0
Order By: Relevance
“…Yan et al (2018) showed that the littoral zones of lakes on the Tibetan Plateau were supersaturated and acted as sources of greenhouse gases. Research on the alpine riverine dissolved inorganic carbon (DIC) of Nyangqu River found that rock weathering controlled the DIC input into the riverine system and groundwater played a significant role in delivering DIC to the surface water (Ge et al, 2021). However, the degassing effect of plateau rivers might be still unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Yan et al (2018) showed that the littoral zones of lakes on the Tibetan Plateau were supersaturated and acted as sources of greenhouse gases. Research on the alpine riverine dissolved inorganic carbon (DIC) of Nyangqu River found that rock weathering controlled the DIC input into the riverine system and groundwater played a significant role in delivering DIC to the surface water (Ge et al, 2021). However, the degassing effect of plateau rivers might be still unclear.…”
Section: Introductionmentioning
confidence: 99%
“…In‐stream CO 2 is controlled by CO 2 exchange with the atmosphere, in‐stream metabolic processes, and input from external sources (Hope et al., 2004; Stumm & Morgan, 1996). The latter includes the import of CO 2 via shallow groundwater exfiltration that originates from root respiration, soil organic matter decomposition, soil CO 2 dissolution, and carbonate weathering (Amiotte‐Suchet et al., 1999; Ge et al., 2021; Hope et al., 2004). On the one hand, several studies report the external input of CO 2 as the major contributor to the overall pool in the water column of rivers and streams (Gu et al., 2021; Peter et al., 2014; Rovelli et al., 2022).…”
Section: Introductionmentioning
confidence: 99%